Analisis Sifat Inferioritas Dan Superioritas Pada Tokoh Yoga dalam novel 7 Prajurit Bapak Karya Wulan Nuramalia - Nur Fadila; Wulaan Nurjanah; Eva Dwi Kurniawan (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2024)
Abstract. The aim of this research is to describe the forms of inferior and superior attitudes of the main character in the novel 7 Warrior Bapak by Wulan Nuramalia in terms of Alfred Adler's individual psychology regarding how humans move through their natural nature, namely inferior, towards superiority or success. The problem raised is what the inferior and superior attitudes of the main character of the novel are like. This research includes descriptive qualitative research. The data source for this research is the novel 7 Soldiers Mr by Wulan Nuramalia by reading and writing. The method used uses library research. This analysis uses Alfred Adler's individual psychology theory, especially those related to inferior and superior. The results obtained show that there are several forms of inferiority attitudes towards the Yoga character in the novel 7 Soldiers, as well as the success or superiority of the Yoga character in realizing his ideals.